Risk factors of negleted diseases at juai district of balangan regency, south kalimantan: a lymphatic filariasis - Dina Amalia Pratiwi; Rina K. Kusumaratna (Jurnal Biomedika dan Kesehatan, 2022)
BACKGROUND 65% of all lymphatic filariasis (LF) could be found in South East Asia, including Indonesia. As one of neglected tropical diseases, filariasis has a major problem on public health and 72% of districts are endemic areas. The clinical manifestation has a major impact on social, economic burden and decreasing quality of life. Aim of the study to explore and determine an influences factors based on social determinant of health among inhabitants at Juai district.METHODSThis research was conducted by using a standardized questionnaire. A two phase of an observational study, firstly a cross-sectional conducted at 3 villages among suspected screening subjects from March to May 2014. The diagnosis of infection was confirmed by finger prick test, which was done from 10 PM until 2 AM. Second phase, a case-control study from October 2014 to January 2015, were obtained from data-based of affected patients and their neighborhoods, comprising 38 subjects respectively. Statistical analysis was descriptive and analytical by chi-square test and multivariate logistic regression. RESULTSFirst phase found 100% of 64 subjects were positive with the count varies from 3 up-to 34 microfilaria. The second phase, LF incidence was significantly associated with age (OR=5.32, 95% CI:1.99-14.16), occupation (OR=3.04, 95% CI:0.95-9.75), less knowledge (OR=3.75, 95% CI:1.37-10.26) and presence of water hyacinths (OR=3.32, 95% CI:1.3-8.54). Only physical environment score were significantly associated (p=0.00) and demonstrably as a protected against LF (OR=0.3, 95% CI:0.10–0.69). CONCLUSIONThe risk of filariasis incidence with good score of physical environment as a protective factor in risk population